On activity ISO/REMCO Committee on reference materials and 39th ISO/REMCO meeting in Russian Federation - E. V. Osintseva; N. I. Koroleva (Стандартные образцы)
The article deals with the results of 39th ISO/REMCO Committee on reference materials meeting (14-16 June 2016, Ekaterinburg, Russian Federation). The meeting was moderated by Federal Agency on Technical Regulating and Metrology (Rosstandart) and Ural Research Institute for Metrology (UNIIM). 37 representatives from 19 countries took part in the meeting (Australia, Belgium, Brazil, Great Britain, Germany, Israel, Kazakhstan, Canada, China, Korea, Netherlands, Russia, USA, Ukraine, France, Czech Republic, Switzerland, Republic of South Africa, Japan) including representatives of national authorities on metrology and national institutes for metrology which cooperate with ISO/REMCO organizations (EDQM, ILAC, CITAC, OIML, UILI) and other ISO technical committees. The meeting dealt with the following issues: final version development of ISO 17034 "General requirements for the competence of reference material producers" (instead of ISO Guide 34-2009) (ISO/CASCO/JWG 43); final version development of ISO Guide 35 "Reference materials - Guidance for characterization and assessment of homogeneity and stability" (instead of ISO Guide 35:2006) (WG 16); particularities of the characterization of pure materials (AHG4); recent advancements in the assessment of homogeneity and stability for reference materials (AHG5); development of the technical report for development of nominal properties reference materials; informational support of ISO/REMCO activities. Finally the resolutions were adopted to accomplish till the next ISO/REMCO meeting